Preparation of layer-aligned graphene composite film with enhanced thermal conductivity. (April 2017) - Liu, Wenqi; Song, Ningning; Wu, Yue; Gai, Yanzhe; Zhao, Yaping
Abstract: The graphene-based composite paper with high thermal conductivity has attracted increasing attention for many potential applications in thermal management systems. In this paper, we reported a pristine-graphene based poly vinyl alcohol (PVA) composite film with high thermal conductivity. Firstly, a concentration of the PVA aqueous solution was mixed with the pristine-graphene made by a green way of supercritical CO2 exfoliation to form the composite solution via non-covalent. Then, the composite solution was filtered through a porous cellulose filter membrane (CFM) by using a vacuum dead-end micro-filtration method. Finally, the film was obtained by peeling from CFM after drying. The characterization results indicate that the as-produced film had a layer-aligned structure and well flexibility. The graphene content of the films varied from 20 wt% to 65 wt%, and their thermal conductivity varied between 10.15 and 36.81 W/mk. The results of dissipating heat indicated the film with 20 μm thickness and 50 wt% graphene loading enabled the temperature of heat source to reduce by 8 °C, suggesting it can be potentially applied in thermal management system. Highlights: Pristine graphene was prepared and could be uniformly distributed in PVA aqueous assisted with SDBS. A vacuum dead-end micro-filtering method was developed to prepare graphene-PVA composite film. The film had a layer-aligned structure in which conductivity network was formed well. The film had excellent thermal conductivity, flexibility and heat dissipation performance.